The role of ceRNAs in breast cancer microenvironmental regulation and therapeutic implications - Yilmaz, Alper; Yuka, Selcen Ari (SPRINGER HEIDELBERG, 2025)
The tumor microenvironment, which is the tailored physiological milieu of heterogeneous cancer cell populations surrounded by stromal and immune cells as well as extracellular matrix components, is a leading modulator of critical cancer hallmarks and one of the most significant prognostic indicators in breast cancer. In the last few decades, with the discovery of the interactions of ncRNAs with diverse cellular molecules, considerable emphasis has been devoted to understanding their direct and indirect roles in specific functions in breast cancer. Collectively, all of these have revealed that the competitive action of protein-coding RNAs and ncRNAs such as circRNAs and lncRNAs, which have a shared affinity for miRNAs, play a vital role in the molecular regulation of breast cancer. This phenomenon, termed as competing endogenous RNAs (ceRNAs), facilitates modeling the microenvironment through intercellular shuttles. Microenvironment ceRNA interactions have emerged as a frontier in the deep understanding of the complex mechanisms of breast cancer. In this review, we first discuss cellular ceRNAs in four key biological processes critical for microenvironmental regulation in breast cancer tissues: hypoxia, angiogenesis, immune regulations, and ECM remodeling. Further, we draw a complete portrait of microenvironment regulation by cell-to-cell cross-talk of shuttled ceRNAs and offer a framework of potential applications and challenges in overcoming the aggressive phenotype of the breast cancer microenvironment.
Keywords: Competing endogenous RNA; circRNA; lncRNA; miRNA; Breast cancer microenvironment; PROMOTES; PROGRESSION; TUMORIGENESIS; METASTASIS; GLYCOLYSIS; NETWORKS; DATABASE; GROWTH; Genetics & Heredity; Research & Experimental Medicine